Nerve stimulator-guided thoracic paravertebral block for gynecomastia surgery - Ashok Jadon (Indian Journal of Anaesthesia, 2012)
Thoracic paravertebral block (TPVB) is gaining popularity for female breast surgeries due to various advantages like less nausea and vomiting and better post-operative pain relief, which helps in early ambulation and discharge from the hospital. Use of nerve stimulator during this block has further enhanced its success and safety profile. Male breast surgery is usually done either under general anaesthesia or local infiltrative anaesthesia combining with intravenous sedation. We postulated that the advantages of TPVB could be helpful for early mobilization and discharge of minor breast surgery in male patients. However, to our knowledge, there is no such report suggestive of TPVB for exclusive male breast surgery. We used nerve stimulator-guided TPVB for gynecomastia surgery in two patients where general anaesthesia was not feasible. Both patients had successful block and showed good post-operative recovery and were discharged on the same day. They had long post-operative pain relief without any block-related complication. A case report of two such cases of gynecomastia surgery (male breast surgery) done under TPVB is presented.